Analisis Sistem Manajemen Mutu pada Proyek Pembangunan Gedung Perkuliahan UPI Kampus Tasikmalaya - Ramadhan, Nazar Caesar; Meirawan, Danny (Teknik Sipil, Politeknik Negeri Ketapangg, 2025)
This study analyzes the quality management system implementation in the construction project of the UPI Tasikmalaya campus lecture building. Using a qualitative descriptive approach with document analysis, the study evaluates the conformity level of the quality management system with ISO 9001:2015 standards and identifies factors that support and hinder its implementation. Secondary data, including technical specifications, project plans, and quality documents, were analyzed systematically. The findings indicate that most elements of the quality management system meet ISO 8001:2015 standards, especially in the documentation of quality plans and external supplier control. However, internal audit implementation requires improvement to enhance overall quality control. Key hindrances include dependence on external suppliers, delays in supervisor approvals, and inadequate structured inspections. On the other hand, detailed technical specifications, guaranteed materials from official suppliers, and a well-defined project team structure are significant supports. The study concludes that implementing a comprehensive internal audit system and structured field inspections can optimize quality management. Recommendations include diversifying material suppliers, simplifying approval processes, and enhancing routine quality monitoring.